2021
DOI: 10.3389/fonc.2020.585551
|View full text |Cite
|
Sign up to set email alerts
|

MYBL2-Driven Transcriptional Programs Link Replication Stress and Error-prone DNA Repair With Genomic Instability in Lung Adenocarcinoma

Abstract: It has long been recognized that defects in cell cycle checkpoint and DNA repair pathways give rise to genomic instability, tumor heterogeneity, and metastasis. Despite this knowledge, the transcription factor-mediated gene expression programs that enable survival and proliferation in the face of enormous replication stress and DNA damage have remained elusive. Using robust omics data from two independent studies, we provide evidence that a large cohort of lung adenocarcinomas exhibit significant genome instab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Given this, elevated expression of MYBL2 mRNA is a robust marker of cells that are arrested prior to mitosis. In this study and our previous work, we have demonstrated that MYBL2 expression is tightly associated with the transcriptional upregulation of DNA repair genes that sense replication stress (12). This fits well when considering the mechanisms through which these signaling pathways coordinate cell cycle arrest following replication stress.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Given this, elevated expression of MYBL2 mRNA is a robust marker of cells that are arrested prior to mitosis. In this study and our previous work, we have demonstrated that MYBL2 expression is tightly associated with the transcriptional upregulation of DNA repair genes that sense replication stress (12). This fits well when considering the mechanisms through which these signaling pathways coordinate cell cycle arrest following replication stress.…”
Section: Discussionsupporting
confidence: 88%
“…SBS4 features increased C>A transversions and is the byproduct of tobacco-smoke induced lesions (20). Importantly, MYBL2 High LUAD carried heterozygous losses in XPC and POLK which impair cellular ability to repair smoking induced lesions through NER (12). This analysis supports the notion that heterozygous losses of repair effectors functionally decrease pathway efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work from our group revealed that elevated expression of the transcription factor MYB proto-oncogene like 2 (MYBL2) identified lung adenocarcinomas with genomic instability and wildtype BRCA [ 13 ]. In this manuscript, we sought to identify a pan-cancer mechanism that underpins genomic instability and cancer progression in BRCA-wildtype tumors.…”
Section: Introductionmentioning
confidence: 99%
“…MYBL2 has also been demonstrated to act as an oncogene in numerous studies (14,15). MYBL2 promotes the malignant development of cancer via regulating various cellular processes including apoptosis, proliferation, differentiation, invasion, metastasis, and replication stress (12,(16)(17)(18)(19)(20). The aberrant expression or dysfunction of MYBL2 has been validated in a variety of cancers including adult leukemia, breast cancer, prostate cancer, ovarian cancer, liver cancer, and lung cancer (19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%